Non-epidemic vibrios and Vibrio Cholerae O1 associated WITH acute diarrhea from cases given during "El Niño" Southern Oscillation (ENSO) 1998. Hospital Nacional Dos de Mayo - Ibarra Trujillo, Jimmy (1999)
OBJECTIVE: Isolation and identification of Vibrio cholerae O1 and non-epidemic Vibrio species associated with acute diarrhea (AD) during the 1998 "El Niño" Southern Oscillation (ENSO). MATERIAL AND METHODS: During 1998 summer months, 70 stool samples from AD patients admitted in Hospital Nacional Dos de Mayo emergency room of Lima were cultured; TCBS Agar isolates were studied. Biochemical and serological tests were performed for identification of Vibrio cholerae O1. Non-epidemic vibrios and others pathogenic vibrios identification was performed according to Bergey’s Bacterial Systematic Manual (1994). RESULTS: Most cases were associated to Vibrio cholerae O1 as unique etiologic agent (64,3%) or related to the others Vibrio species (4,2%). Two cases involving Vibrio vulnificus (2,9%) and 3 with V. parahaemolyticus (4,3%) as etiologic agents of AD, are described. CONCLUSIONS: Vibrio cholerae O1 association with others non-epidemic vibrios lets us assume a direct relationship between evaluated diarrheic infections and ENSO.